2020
DOI: 10.1038/s41586-020-2689-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the human DPR core promoter element using machine learning

Abstract: The RNA polymerase II (Pol II) core promoter is the strategic site of convergence of the signals that lead to transcription initiation 1 - 5 , but the downstream core promoter in humans has been difficult to decipher 1 - 3 . Here, we analyze the human Pol II core promoter and use machine learning to generate predictive models for the downstream core promoter region (DPR) and the TATA box. We developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 36 publications
1
67
0
Order By: Relevance
“…The latter was critical to minimize sequence biases originating from the high GC content in promoter-proximal gene regions ( 85 ). Interestingly, the promoter-proximal pause motif shows similarities to the consensus sequence of the following core promoter elements located downstream of the TSS ( 86 , 87 ): the downstream core promoter element (DPE) ( 88 ), the downstream core element (DCE) ( 89 , 90 ) and the recently uncovered human DPR core promoter element ( 91 ) ( Supplementary Figure S6B ). The region where these cis -elements are located strongly overlap with the region where promoter-proximal pausing of Pol II usually occurs.…”
Section: Discussionmentioning
confidence: 95%
“…The latter was critical to minimize sequence biases originating from the high GC content in promoter-proximal gene regions ( 85 ). Interestingly, the promoter-proximal pause motif shows similarities to the consensus sequence of the following core promoter elements located downstream of the TSS ( 86 , 87 ): the downstream core promoter element (DPE) ( 88 ), the downstream core element (DCE) ( 89 , 90 ) and the recently uncovered human DPR core promoter element ( 91 ) ( Supplementary Figure S6B ). The region where these cis -elements are located strongly overlap with the region where promoter-proximal pausing of Pol II usually occurs.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the experiments were performed in two different cell lines, using different readout as the outcome, either the indirect luciferase reporter activity (this study) or the RNA output itself, using either RNAseq or primer extension analysis [55]. Surprisingly, the two independent approaches identified functional downstream positions/region within the ANP32E promoter.…”
Section: Discussionmentioning
confidence: 98%
“…During the preparation of the manuscript, we became aware of a comprehensive work from the Kadonaga lab [55], which used machine learning to generate predictive models to analyze human Pol II core promoters and identified a downstream promoter region (DPR) spanning from +17 to +35, which contributes to the transcriptional output of a fraction of human promoters. Reassuringly, the positions identified in our study highly match specific positions within the DPR identified by the Kadonaga lab, which supports the concept of a single functional downstream unit [30, 52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations